Kontribusi Sarana Prasarana Pendidikan, Kondisi Lingkungan, Kedisiplinan Kerja Terhadap Kinerja Guru SD - Sutama, Sutama; Kristiawanto, Kristiawanto; Suyatmini, Suyatmini (Universitas Muhammadiyah Surakarta, 2016)
This study aims to examine the contribution of education infrastructure, environmental conditions, and work discipline teacher performance UPTD Pendidikan Kecamatan Brati Â simultaneously and partially. This research is quantitative. The population of this study were 188 elementary school teachers then retrieved a sample of 128 teachers through proporsional random sampling. The technique of collecting data using questionnaires. Data were analyzed using multiple linear regression analysis, test the accuracy of the model, test the accuracy of parameter estimators (t test), donations predictors and classical assumption. Results of the study: 1) the infrastructure of education, the environment and simultaneously work discipline has contributed to the performance of elementary school teachers in the District UPTD Brati with Î± 5% is a significant level of value 1,657 0,000 <0,05 and the effective contribution of 74.68%. 2) Means of education infrastructure showed a significant influence on the performance of teachers with sig 0.000 <0.05 and the effective contribution of 25.93%. 3) Environmental conditions showed no significant effect on the performance of teachers with sig 0.000 <0.05 and the effective contribution of 11:03%. 4) Discipline work shows significant effects on the performance of teachers with sig 0.000 <0.05 and the effective contribution of 37.72%. 5) The independent variable a contribution of 84.4% of the performance of teachers and 15.6% are influenced by other factors not discussed in this study.